ANALISIS BIAYA DALAM MENENTUKAN HARGA JUAL YANG KOMPETITIF - Nawara, Shadiqin; Fikri, Ariful; Rikardo, Diki (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
ABSTRACT In manufacturing companies whose main activity is to produce, it is very important to do cost calculation techniques. Methods that have a significant influence are Least Square and Cost-volume-profit. Least Square and Cost-volume-profit methods can help business entities to determine competitive selling prices on the market. Taking into account the cost analysis that can provide a major influence on management decisions within the company. The existence of this method is very important in manufacturing companies. Especially in controlling and controlling the cost drivers in production activities. However, overall management also considers the profits the company gets in each period. And management also needs to determine the target unit of production that must be achieved. With the number of activities that occur in manufacturing companies, of course the costs incurred are also increasingly numerous and varied. Thus, the Least Square method and Cost-volume-profit are very important. obtained from the results of the analysis will be used by company management both now and in the future.